The Investment Capacities of the Ukrainian Economy the EU countries - Bilousova, O. S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article deals with selected aspects of investment in the context of the enhanced competition at investment markets and the need to increase the investment performance. A review of literary sources shows that investment capacities essentially refer to the economy’s capability to fund processes or phases related with generation of innovation, formation and modernization of fixed assets or intangible assets; development of education, research and information sectors; reproduction, support and creation of national wealth. It is emphasized that formation and realization of investment capacities in the economy can be attributed to processes that have significant effects for economic performance in the long run, especially when the capacities are innovative. The author’s definition of investment capacities of the economy is given, as the capacity to support financially the upward investment trend through accumulating fixed capital and increasing the profit rate from its generation in current and medium-term periods. The existing methodology for assessment of investment capacities at country level is analyzed; recommendations to improve the system of aggregated investment statistics, taking into account the Eurostat methodology, are given. Statistical indicators measuring the investment capacities in EU countries and Ukraine are analyzed. The analysis shows that the investment rate in Ukrainian industrial enterprises was 21.8% in 2014 and 19.6% in 2015, giving an indication of downward investment trend and the shrinking investment capacities of the national economy. Growth in the share of profit in the value added in 2015 by 6.7 percentage points (to 47.3%) compared with 2014 is evidence that instead of investing internal resources, enterprises use them to cover financial loses or tend to take them off the national boundaries. Upward investment trend can be recovered by the increased supply of investment projects with low level of investment risk and high return and profit rate.